Characteristics of various hydrogel for gas adsorption purposes: article - Abdullah, Noor Adilla; Talib, Mdm Norhayati (2019)
Carbometycellulose (CMC) is water soluble polymer that capable to hold large water uptake because of superabsorbent characteristic of the polymer. Starch is used to decrease the cost of preparation of the CMC/starch hydrogel. Biodegradable CMC/starch hydrogel is synthesized by irradiation in high concentrated solution. CMC/starch hydrogel is induced by irradiation to create crosslinking between starch and CMC. The swelling abilities of hydrogel are investigate based on effect of gamma doses and starch concentration. The hydrogel biochar also conducted with varies the content of fly ash to know the effect of fly ash towards the performance of the hydrogel. Biochar is a good adsorption for removal of heavy metal because of high carbon content. Biochar is used as raw material to replace the activated carbon to minimize the cost in preparing the hydrogel. Biochar is produced by heating the biomass at high temperature in close surrounding with absent air. Then, the content of fly ash will vary to the content of biochar. The biomass used as feedstock is sugarcane bagasse because one of agricultural wastes that eco-friendly, contain high fibre and not involve cost for purchasing. This study is to give characteristic to CMC/Starch hydrogel and biochar hydrogel by doing analysis on thermogravimetric(TGA), Brunauer-Emmette-Teller (BET), degree of swelling and FTIR absorption analysis. The both type of hydrogel is compared to know the best adsorbent and absorbent. The superabsorbent hydrogel is CMC/Starch hydrogel with 20kGy gamma doses and hydrogel biochar with no fly ash. The good adsorbent is CMC/Starch hydrogel with 10kGy and hydrogel biochar with 50wt% of biochar and 50wt% of fly ash. The best adsorbent and absorbent is proving by analysis of degree of swelling and surface area of the hydrogel